Causes and Effects of Examination Malpractice on Social Studies Students in Secondary Schools of Apa Local Government Area of Benue State, Nigeria - Irmiya, Ruth A.; Lukman, Shittu (NIU Journal of Social Sciences; Vol 5 No 1 (2019): KIU Journal of Social Sciences, Vol. 5 No. 1, March 2019, 2019)
This paper looks into the causes and effects of examination malpractices on academic performance of Social Studies students in some secondary schools in Jos Metropolis in Plateau State, Nigeria. The background looked into issues of malpractice and degrading standard of Nigeria education. The statement of problem also pinpoint the problems bothering effects examination malpractices can have on students as well. Three research questions where formulated to guide the study which include: causes of malpractice among social studies students among others. The population and samples used for the study consists of 200 students and 50 teachers’ randomly selected from the study area. While the method of data analysis applied was descriptive inferential statistics particularly the mean method. The study revealed that lack of professional teachers, teaching materials and emphasis on certification as well as examination have been the only means of evaluation and thus are of the major reasons why students engage in examination malpractice in the study area. Again the researchers further revealed that parents, government, teachers and even the communities are partakers in examination malpractices. The study makes some recommendations to include, qualified social study teachers should be employed, teachers’ welfare should be properly taken care of and their remuneration prioritized, government should punish partakers of malpractices when cut among others. Keywords: Causes and effects, examination malpractice, social studies students and secondary schools